Efficient expropriation: Sustainable fiscal policy in a small open economy - Mark Aguiar; Manuel Amador; Gita Gopinath (Federal Reserve Bank of Boston, 2006)
We study a small open economy characterized by two empirically important frictions- incomplete financial markets and an inability of the government to commit to policy. We characterize the best sustainable fiscal policy and show that it can amplify and prolong shocks to output. In particular, even when the government is completely benevolent, the government's credibility not to expropriate capital varies endogenously with the state of the economy and may be scarcest during recessions. This increased threat of expropriation depresses investment, prolonging downturns. It is the incompleteness of financial markets and the lack of commitment that generate investment cycles even in an environment where first-best capital stock is constant.
Keywords: C91; C93; D01; D64; 330